2011
DOI: 10.1108/03090561111095658
|View full text |Cite
|
Sign up to set email alerts
|

The role of brand image, product involvement, and knowledge in explaining consumer purchase behaviour of counterfeits

Abstract: Purpose -Counterfeiting has become a significant economic phenomenon. Increased demand for counterfeit branded products (CBPs) makes the study of determinants of consumers CBPs purchase behaviour more worthwhile than ever before. Existing studies have largely neglected brand influence on consumer purchase behaviour of CBPs. This research seeks to examine the impact of perceived brand image, direct and indirect effects (mediator and moderator effects) of product involvement and product knowledge on consumer pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
262
2
21

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(294 citation statements)
references
References 86 publications
9
262
2
21
Order By: Relevance
“…Brand image significantly contributed to the decision to buy or not to buy that brand personally (Bian & Moutinho, 2011). also indicate if luxurious goods on which consumers know about its brand and reputation, they will tend to favor its counterfeiting.…”
Section: Brand Image and Attitudesmentioning
confidence: 99%
“…Brand image significantly contributed to the decision to buy or not to buy that brand personally (Bian & Moutinho, 2011). also indicate if luxurious goods on which consumers know about its brand and reputation, they will tend to favor its counterfeiting.…”
Section: Brand Image and Attitudesmentioning
confidence: 99%
“…It was found that knowledge of procedure has the greatest influence on the students' readiness to venture into business of all the three factors. The insignificant relationship between product knowledge and readiness to venture may be due to the effect of several factors, such as inferior perceived brand image (Bian & Moutinho, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Product involvement has been used as a moderating or explanatory variable and considered a central framework, which is crucial for the understanding of consumer decision-making behaviour and associated communications (Bian and Moutinho, 2011). We argue that the relevance of a product, in turn, is influenced by its luxury level and its purchase frequency.…”
Section: Luxury Level Purchase Frequency and Product Involvementmentioning
confidence: 99%
“…A high degree of product involvement, therefore, implies that customers attribute a high value to the product. Moreover, research has shown that a product's personal relevance influences consumers' motivation to process information about it (Bian and Moutinho, 2011). Luxury products, that "tend to be more distinctive, higher priced, and unique" [Broekhuizen and Alsem, (2002), p.320] are less frequently purchased and consequently higher valued.…”
Section: Luxury Level Purchase Frequency and Product Involvementmentioning
confidence: 99%